Assessment of otological and audiological status in patients of allergic rhinitis - Kumar, Sanjeev; Singh, Hitendra Prakash; Kumar, Sunil; Verma, Veerendra; Mishra, Anupam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Allergic rhinitis (AR) is a type-I hypersensitivity reaction of the nasal mucosa to the airborne allergens, primarily mediated by immunoglobulin E (IgE) characterized by nasal obstruction, watery rhinorrhea, sneezing and itching at the nose, palate and nasopharyngeal region. Various studies have been done to study the relationship between middle ear afflictions and allergic rhinitis and majority of them incriminate nasal allergies as a probable factor to the development of otitis media. Methods: A total of 70 patients, affected by allergic rhinitis, were recruited for the study after fulfilling the inclusion and exclusion criteria. Complete audiological work up including tympanometry studies was performed. Patients’ data was then compiled and analyzed using statistical analyses. Results: It was observed that disease is more common in age group of 21 to 30 years. 63% patient had perennial allergic rhinitis and rest 37% had seasonal allergic rhinitis. Otoscopic examination of the participants revealed that abnormal tympanic membrane findings such as retracted, congested, bulged and dull TM is more common in PAR than SAR. Hearing impairment is more common in PAR than SAR. Tympanometry study showed that in PAR ‘B’ type of tympanogram was found in 20% cases and ‘C’ type curve was found in 19% cases while in SAR these value were 4% and 8% respectively. Conclusions: Allergic rhinitis whether seasonal or perennial adversely affect the eustachian tube functions which in turn may lead to increased incidence of middle ear effusion and otitis media. Diagnosis and proper management of allergic rhinitis is the key to avoid these middle ear diseases.